Level Of Knowledge, Attitude, And Practice Of Personal Hygiene Were Not Correlated With Pediculosis Capitis - Azizah, Zakiah; Kesetyaningsih, Tri (Universitas Muhammadiyah Yogyakarta, 2023)
Introduction – Pediculosis capitis is the most common ectoparasitosis in the world, transmitted by direct contact. Pediculosis capitis is more common in girls and has a high prevalence in command environment. The results of research on personal hygiene as a risk factor for pediculosis capitis are still inconsistent. Purpose – This study aims to analyze the relationship between the level of knowledge, attitude, and practice of personal hygiene with the incidence of pediculosis capitis in Islamic boarding schools. Methodology/Approach – This research is an analytic observational with a cross sectional design. The research was conducted at Pesantren X in Magelang and was carried out after obtaining research ethic approval. Respondents are female students, taken by total population sampling. Data on the level of knowledge, attitudes, and personal hygiene practices were obtained through a questionnaire, while the diagnosis of pediculosis was obtained by examining the hair and scalp directly. Data scores of Knowledge, Attitudes, and Personal Hygiene Practices were categorized into good, medium, and low. Data were analyzed using chi-square to determine the relationship between the level of knowledge, attitudes, and personal hygiene practices with the incidence of pediculosis capitis. Findings – There were 78 research respondents who met the inclusion criteria. The results showed that 52 students (66.67%) suffered from pediculosis capitis. Regarding personal hygiene, as many as 60 people (76.92%) have good knowledge, 43 (55.13%) are good and 59 (75.64%) have good practices. The results of statistical analysis showed that there was no relationship between the level of knowledge (p = 0.08), attitude (p = 0.52) and practice (p = 0.70) of personal hygiene with the incidence of pediculosis capitis. It was concluded that knowledge, attitude and practice of personal hygiene in Pondok Pesantren X was not a risk factor for the incidence of pediculosis capitis. Implication – Knowledge, attitudes, and personal hygiene practices cannot be used to prevent the occurrence of pediculosis capitis in Islamic boarding school students X.